The development of human resource practitioner competency model perceived by Malaysian human resource practitioners and consultants - Abdul Hamid, Abdullah (2010)
The development of HR competency models/frameworks is an area that has gained a great deal of interest over the years. Most of the notable HR competency models are developed in the US and Europe. HR competency models can assist HR Practitioners to observe their tasks and work dimensions, the competencies they are expected to acquire, and hence profess them. The aim of the study was to develop an empirically substantiated HR Practitioner Competency Model. The HR Practitioner Competency Model with significant competencies was developed through the administration of a self developed survey questionnaire and the target respondents were the HR practitioners and HR consultants in Malaysia. The study undertaken is an extrapolation of the notable studies carried out primarily by Brewster et al. (2000), Brockbank and Ulrich (2003), and Ulrich et al. (2008). The competency domains in the generic/behavioural competency category, business competency category, and the technical HR competency category were analysed using Exploratory factor analysis (EFA), Confirmatory factor analysis (CFA), and Structural equation modeling (SEM). Altogether 12 competency domains and 103 items were analysed. The competency categories significant in the study were the generic/behavioural competency category and the technical HR competency category. The business competency category was not significant in the study. The competency domains significant in the HR Practitioner Competency Model were: relationship building and process drivers; personal credibility and attributes; resourcing and talent management; and employee relations and compliance. Altogether 14 competency factors were significant in the study and these include process management, flexibility, information seeking, strong initiative, pride at work, pro-activeness, iii ability to change, leadership, organisation development, career planning, succession planning, human performance improvement, discipline, and occupational safety and health. The empirically tested HR Practitioner Competency Model was derived in a local Malaysian cultural setting and it will benefit the HR practitioners, HR consultants, HR communities of practice, the academia, organisations, and other related individuals.